Tomato flu-a tell-tale sign of another pandemic or just a benign manifestation of hand foot mouth disease - Kumar, Rajan; Kumar, Suman; Kumar, Deepak (International Journal of Contemporary Pediatrics, 2022)
The world is still dealing with the COVID-19 pandemic, but of a gentle variant. In the midst of the global crisis, in God's own land (Kerala), media highlighted cases of febrile illness similar to flu with red round skin lesions that bear a resemblance to tomatoes that have emerged in children younger than 5 years, known as tomato flu or tomato fever. It could be an aftereffect of chikungunya or dengue, rather than a new viral illness. Numerous reports claim that the tomato flu is truly a viral HFMD variant. Hand, foot, and mouth disease (HFMD) is a common febrile illness characterised by a rash caused by enteroviruses, including Coxsackie A16 (CA16), EV A71, Coxsackie A6, Coxsackie B, and Echo viruses.